Total laparo-endoscopic single site surgery hysterectomy for endometrial cancer: a single-centre retrospective review - Cheah, Grace Hui Shi; Chin, Hui Men Selina; Chia, Eik Chao; Nadarajah, Ravichandaran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: LESS surgery is a novel technique for benign gynaecological conditions. It has advantages of shorter operative stay, less post-operative pain, better cosmesis, and improved patient satisfaction. However, similar data is limited in endometrial cancer. This study aims to analyse the peri- and post-operative outcomes of LESS surgery for endometrial cancer. Methods: This was a retrospective, single-centre study. One gynae-oncologist trained in minimally invasive surgery performed 97 cases of LESS surgery for endometrial cancer at Singapore General Hospital, Singapore from January 2018 to December 2023. Results: 97 patients were recruited for this study. At the time of pre-operative staging, 72 women were Stage IA, and 22 IIB. All underwent total hysterectomy bilateral salpingo-oophorectomy, with 90 and three patients undergoing pelvic and para-aortic lymphadenectomy respectively. A median of 18 pelvic lymph nodes (IQR 13-21) were retrieved. The median operative time and operative blood loss was 165 minutes (IQR 130-196.25) and 100mls (IQR 50-150) respectively. The median hospitalization stay was 2 days (range 1-7). Two women were readmitted for ileus (POD20) and post-op fever secondary to urinary tract infection (POD14), both of which were managed conservatively. The median duration of follow up was 24.5 months. There was 1 reported case of recurrence. There were three deaths in this study. Conclusions: Women with early-stage endometrial cancer should be offered LESS surgery. It is a safe and effective surgical option for the management of endometrial carcinoma.